Acceleration of new medicines-CMC lessons learned from emergency use authorizations - James Bernstein; Kim Huynh-Ba; Patrick Lynch; Thomas Oliver; Reza Oliyai; Scott W. Roberts; Andrea Schirmer; David Schwinke; Kin Tang; Jessica Ursin (SpringerOpen, 2024)
Abstract The American Association of Pharmaceutical Scientists (AAPS) Chemistry, Manufacturing, and Control (CMC) Community hosted a virtual panel discussion on July 15, 2022, to provide a forum to discuss industry and regulator CMC challenges associated with emergency use authorizations.